(untitled) (The Conference Hub, 2025)
This article analyzes the anthropological views of the great scholar and encyclopedist Abu Rayhan Beruni. Beruni’s thoughts on man and society, his cross-cultural comparative approach, ethnographic observations and scientific methods are studied in comparison with modern anthropology. In particular, his information about the customs, religious beliefs and lifestyles of different peoples described in his work "India" is considered one of the most important contributions to this field. The article highlights the compatibility of Beruni’s views with the principles of human equality, cultural tolerance and scientific objectivity. Through these scientific and theoretical analyses, it is proven that Beruni’s anthropological thought has not lost its relevance even today.